COMPARISON FLUORIDE CONCENTRATION IN SALIVA BETWEEN FLUORIDE VARNISH AND GLASS IONOMER CEMENT - Dewiyani, Sari; Paath, Stanny Linda; Febrianti, Fitria (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Caries is one of the most common dental diseases. Caries prevention by improving dental health has become a major goal in the world of dentistry.Topical application of fluoride is one of the most effective ways to prevent caries.Glass ionomer cement and fluoride varnish has the effect of preventing dental caries because these materials release fluoride. There is no better treatment for demineralization than prevention itself. One of these steps is the combination of dental restorative materials with the application of topical fluoride as an additional source of fluoride.Method: A total of 32 permanent premolar teeth samples, immersed in artificial saliva before and after the application of fluoride varnish and glass ionomer cement. The measurement of fluoride levels in saliva was carried out using a spectrophotometric tool.Result: Independent T-test results obtained sig. below 0.05 indicates that there are differences in the level of fluoride levels between the fluoride varnish group and the glass ionomer cement.Conclusion: Fluoride varnish and glass ionomer cement can increase fluor concentration in salivaÂ